VKORC1 haplotypes and their impact on the inter-individual and inter-ethnical variability of oral anticoagulation - Geisen, Christof; Watzka, Matthias; Sittinger, Katja; Steffens, Michael; Daugela, Laurynas; Seifried, Erhard; Müller, Clemens R.; Wienker, Thomas F.; Oldenburg, Johannes (Thrombosis and Haemostasis, 2005)
In order to elucidate the role of VCORC1 sequence variants in warfarin sensitivity, we established a complete SNP map of the VKORC1 gene locus in 200 blood donors from Western Germany. Nearly all of the genetic variability of the VKORC1 gene in Europeans is reflected by three main haplotypes. Recently described polymorphisms associated with low warfarin dose requirement (dbSNP:rs9934438; dbSNP:rs17878363) were found in complete linkage disequilibrium with the VKORC1*2 haplotype. In two patient cohorts of European origin with either increased coumarin sensitivity (n=14) or partial coumarin resistance (n=36) the VKORC1*2 frequency varied highly significant between the two groups and also when compared to 200 blood donor controls (coumarin sensitive 96%, coumarin resistant 7%, controls 42%) thus demonstrating a strong association between these two phenotypes and the VKORC1 haplotype (p = 1.6 x 10−8 for coumarin sensitive and p = 1.9 x 10−8 for coumarin resistant). Analysis of database derived VKORC1 genotypes of African Americans and Chinese revealed that haplotype frequencies in these populations differ significantly from the European sample (for VKORC1*2: Europeans 42%, Chinese 95%, African Americans 14%). These observations suggest VKORC1 as principal genetic modulator of the ethnic differences in warfarin response. Since hereditary pharmacodynamic (VKORC1) and pharmacokinetic (CYP2C9) factors account for up to 50% of the inter-individual variability of the warfarin response, these genetic markers may serve as clinically relevant predictors of warfarin dosing in future studies.
Keywords: Vitamin K epoxide reductase; VKORC1; warfarin; vitamin K; haplotype